Self-Powered Chemical Sensing Driven by Graphene-Based Photovoltaic Heterojunctions with Chemically Tunable Built-In Potentials - Lee, Donghun; Park, Haeli; Han, Soo Deok; Kim, Su Han; Huh, Woong; Lee, Jae Yoon; Kim, Yoon Seok; Park, Myung Jin; Park, Won Il; Kang, Chong-Yun; Lee, Chul-Ho (WILEY-V C H VERLAG GMBH, 2019)
Ultralow power chemical sensing is essential toward realizing the Internet of Things. However, electrically driven sensors must consume power to generate an electrical readout. Here, a different class of self-powered chemical sensing platform based on unconventional photovoltaic heterojunctions consisting of a top graphene (Gr) layer in contact with underlying photoactive semiconductors including bulk silicon and layered transition metal dichalcogenides is proposed. Owing to the chemically tunable electrochemical potential of Gr, the built-in potential at the junction is effectively modulated by absorbed gas molecules in a predictable manner depending on their redox characteristics. Such ability distinctive from bulk photovoltaic counterparts enables photovoltaic-driven chemical sensing without electric power consumption. Furthermore, it is demonstrated that the hydrogen (H-2) sensing properties are independent of the light intensity, but sensitive to the gas concentration down to the 1 ppm level at room temperature. These results present an innovative strategy to realize extremely energy-efficient sensors, providing an important advancement for future ubiquitous sensing.
Keywords: SOLAR-CELLS; SENSOR; VOLTAGE; ARRAYS